Village Partnership Program for Health Improvement for the Elderly in Penatarsewu Village, Tanggulangin Sidoarjo - Paramitha Amelia Kusumawardani; Siti Cholifah; Rachmat Firdaus; Hamzah Setiawan; Ribangun Bamban Jakaria (Jurnal Dedikasi, 2020)
Elderly age is an age that is susceptible to various diseases. There are many changes both physically, cognitively, mentally, psychosocial and spiritually and with many of these changes it will be better if the elderly get better services. Services in all aspects for the elderly in Indonesia have not received the maximum touch from the government. Based on the results of the initial survey conducted by the Proposal Team in mid-December 2019 at the Tanggulangin Health Center, it was found that only 42.50% received health services. This shows that the coverage of elderly health services in Penatarsewu village is less than the target set by the Health Office. Therefore, the community service partner and partners improve the health status of the elderly by optimizing home health checks for the elderly and training and mentoring posyandu cadres for the elderly. With this village partnership program, holding a routine elderly posyandu equipped with adequate medical checkups, competent elderly cadres and elderly gymnastics that have been held regularly are the right solution to be carried out in Penatarsewu Village.